A conjugate of a complex number is another complex number which has the same real part as the original complex number and the imaginary part has the same magnitude but opposite sign. If we multiply a complex number with its conjugate, we get a real number. The conjugates of complex numbers give the mirror image of the complex number about the real axis in the argand plane. In this article, we will learn the conjugates of complex numbers and their properties along with solved examples.
A number of the form z = x + iy, where x, y are real numbers is called a complex number. Here x is called the real part and y is called the imaginary part. The imaginary number ‘i’ is the square root of -1. Consider a complex number z = a + ib. The conjugate of this complex number is denoted by
Here, the conjugate (a – ib) is the reflection of the complex number a + ib about the X axis (real-axis) in the argand plane. In polar form, the complex conjugate of the complex number reiθ is re-iθ. To rationalize the complex number, the complex conjugate of a complex number is used. Consider the complex number 3 – 2i. Then the complex conjugate is 3 + 2i. The following figure gives you a clear idea of the conjugate of a complex number.
Properties Of Conjugates Of Complex Numbers
1. The modulus of z is equal to the modulus of
arg z = – arg (
2. If z is purely real, then
3. If z is purely imaginary, then
4. The complex conjugate of the product of two complex numbers is equal to the product of the complex conjugates of the two complex numbers.
5. The complex conjugate of the quotient of two complex numbers is equal to the quotient of the complex conjugates of the two complex numbers.
z2 ≠ 0.
6. If we add a complex number and its conjugate, then the sum is equal to 2Re(z).
If Z = 2/(1-i) then the conjugate of Z is
4) none of these
If Z = x+iy, then conjugate of Z is (x-iy)
Z = 2/(1-i)
Hence, option (1) is the answer.
If (3+ i) (
4) none of these
Suppose z = x+iy
Substituting above values in (i)
(3+i)2x-(2+i)2iy+14i = 0
6x+2ix-4iy+2y+14i = 0
(6x+2y)+(2x-4y+14)i = 0
Comparing real part
6x+2y = 0
6x = -2y
y = 6x/-2
y = -3x
Comparing imaginary part
2x-4y+14 = 0
Put y = -3x in above equation
2x+12x+14 = 0
14x = -14
x = -1
So y = 3
Now z = -1+3i
Hence, option (3) is the answer.